Encyclopedia of Latin America - Leonard, Thomas M., 1937-; Francis, J. Michael (John Michael); Burkholder, Mark A., 1943-; Rankin, Monica A., 1972- (New York : Facts On File, 2010)
"Authoritative yet accessible, the new four-volume Encyclopedia of Latin America covers the history and culture of Central America, South America, and the Caribbean from early settlements to the present day. Each volume focuses on a specific time period in the area's development, beginning with an introduction to the time period, followed by a detailed chronology. A collection of primary source documents at the end of each volume gives a firsthand account of the major developments of the era. A glossary, bibliography, and index in each volume, a cumulative index in Volume IV, and 250 black-and-white images and maps round out this attractive and reliable resource on Latin America."--Page [4] of covers.
v. 1. Amerindians through foreign colonization (prehistory to 1560) / J. Michael Francis, volume editor -- v. 2. From colonies to independent nations (1550s to 1820s) / Mark A. Burkholder, volume editor -- v. 3. Search for national identity (1820s to 1900) / Monica A. Rankin, volume editor -- v. 4. The age of globalization (1900 to the present) / Thomas M. Leonard, volume editor.
Includes bibliographical references and index.
Keywords: Latin America -- History -- Encyclopedias